TEGANGAN GESER ULTIMIT EPOXY-RESIN PADA SAMBUNGAN BALOK KAYU YANG DIBEBANI GAYA TEKAN SEJAJAR SERAT - Putra, Dharma; Sugita, I Nyoman; Padmi, Ni Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 11, No. 2 Juli 2007)
he goal of this research is to study the ultimate shear of Epoxy- resin at wood bar connection due to parallel fibre of wood centric load. Specimens are kamfer wood bar, 15% water content, size 4/20, connected by 2 x 3/ 20 side by side using Epoxy- resin . There are five treatments with the area of Epoxy- resin are 200 cm2 , 400 cm2, 600 cm2 , 800 cm2, 1000 cm2 and two replication each. Specimens is loaded by increament parallel fibre of wood centric load until connection failure. The results show that the ultimate shear stress of Epoxy- resin of each treatment are 3.38 MPa , 3.12 MPa, 3.09 MPa, 3. 25 MPa and 3.4 MPa. The average ultimate shear stress is 3.25 MPa . The Epoxy- resin can be used asa an alternative material for wood connector, has highly efficience and brittle behavior.
Keywords: ultimate shear stress, epoxy–resin ,water content, kamfer wood, centic load